Ruinisation and regeneration in the tourism space of Havana - Kaczmarek, Sylwia (Turyzm/Tourism, 2018)
The author’s aim is to conduct an ethical analysis of degradation and regeneration processes in tourism space, using the example of Havana, Cuba. This is in the context of social relations between tourists and local inhabitants, as well as assessing the significance of regular patterns in these processes and their impact. As a result of the analysis, the author identified the causes of the ruinisation of tourism space in Havana, the exogenous and endogenous factors which influence this process, two types of regeneration undertaken as remedial action, as well as establishing the relationships between local inhabitants and tourists. The research results are followed by commentary indicating those elements of social relations which should be taken into consideration when starting a process of the urban regeneration of tourism space, in order to relieve present and potential conflicts between the inhabitants and tourists.